Of switches and hourglasses: regulation of subcellular traffic in circadian clocks by phosphorylation - Tataroglu, Ozgur; Schafmeier, Tobias (EMBO reports, 2010)
Investigation of the phosphorylation of circadian clock proteins has shown that this modification contributes to circadian timing in all model organisms. Phosphorylation alters the stability, transcriptional activity and subcellular localization of clock proteins during the course of a day, such that time-of-day-specific phosphorylation encodes information for measuring time and is crucial for the establishment of an approximately 24-h period. One main feature of molecular timekeeping is the daytime-specific nuclear accumulation of clock proteins, which can be regulated by phosphorylation. Here, we discuss increasing knowledge of how subcellular shuttling is regulated in circadian clocks, on the basis of recent observations in Neurospora crassa showing that clock proteins undergo maturation through sequential phosphorylation. In this model organism, clock proteins are regulated by the phosphorylation-dependent modulation of rapid shuttling cycles that alter their subcellular localization in a time-of-day-specific manner.
Gesehen am 15.09.2023